Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp - Aguilera-Uribe, Magali; Martínez, Juan José; Zaldívar-Riverón, Alejandro (Zootaxa, 2018)
Three species of the braconid genus Pambolus (Braconidae) are described from Mexico: P. jarocho sp. n., P. chinanteco sp. n. and P. bizelab sp. n. The external morphological variation in males and females of P. oblongispina Papp, previously known only by two females from Honduras and northern Mexico, is described based on material from Jalisco and Oaxaca in central and southeast Mexico. Molecular characterisation of the examined species was carried out based on the 28S nuclear ribosomal and the COI mitochondrial DNA gene markers.